Simultaneously determination of bisphenol a and uric acid by zinc/aluminum-layered double hydroxide 2(2,4-dichlorophenoxy) propionate paste electrode - Nurul Syahida Mat Aris (Tanjong Malim, 2020)
Simultaneously determination of bisphenol a and uric acid by zinc/aluminum-layered double hydroxide 2(2,4-dichlorophenoxy) propionate paste electrode by Nurul Syahida Mat Aris